a)
is conservative if it is the gradient field for some scalar function
. This would require
![\dfrac{\partial f}{\partial x} = e^{y + 2z}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cpartial%20f%7D%7B%5Cpartial%20x%7D%20%3D%20e%5E%7By%20%2B%202z%7D)
![\dfrac{\partial f}{\partial y} = x \, e^{y + 2z}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cpartial%20f%7D%7B%5Cpartial%20y%7D%20%3D%20x%20%5C%2C%20e%5E%7By%20%2B%202z%7D)
![\dfrac{\partial f}{\partial z} = ax \, e^{y+2z}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cpartial%20f%7D%7B%5Cpartial%20z%7D%20%3D%20ax%20%5C%2C%20e%5E%7By%2B2z%7D)
Integrating both sides of the first equation with respect to
yields
![f(x,y,z) = x \, e^{y + 2z} + g(y, z)](https://tex.z-dn.net/?f=f%28x%2Cy%2Cz%29%20%3D%20x%20%5C%2C%20e%5E%7By%20%2B%202z%7D%20%2B%20g%28y%2C%20z%29)
Differentiate with respect to
:
![\dfrac{\partial f}{\partial y} = x \, e^{y + 2z} = x \, e^{y + 2z} + \dfrac{\partial g}{\partial y} \implies \dfrac{\partial g}{\partial y} = 0 \implies g(y, z) = h(z)](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cpartial%20f%7D%7B%5Cpartial%20y%7D%20%3D%20x%20%5C%2C%20e%5E%7By%20%2B%202z%7D%20%3D%20x%20%5C%2C%20e%5E%7By%20%2B%202z%7D%20%2B%20%5Cdfrac%7B%5Cpartial%20g%7D%7B%5Cpartial%20y%7D%20%5Cimplies%20%5Cdfrac%7B%5Cpartial%20g%7D%7B%5Cpartial%20y%7D%20%3D%200%20%5Cimplies%20g%28y%2C%20z%29%20%3D%20h%28z%29)
Differentiate with respect to
:
![\dfrac{\partial f}{\partial z} = ax \, e^{y + 2z} = 2x \, e^{y + 2z} + \dfrac{dh}{dz}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cpartial%20f%7D%7B%5Cpartial%20z%7D%20%3D%20ax%20%5C%2C%20e%5E%7By%20%2B%202z%7D%20%3D%202x%20%5C%2C%20e%5E%7By%20%2B%202z%7D%20%2B%20%5Cdfrac%7Bdh%7D%7Bdz%7D)
We want
to be independent of
and
; we can make them both disappear by picking
.
b) This is the so-called triple product, which has the property
![(7\,\hat\jmath - 4\,\hat k) \cdot \bigg((-2\,\hat\imath+3\,\hat k) \times (\hat\imath + 2\,\hat\jmath-\hat k)\bigg) = \det \begin{bmatrix} 0 & 7 & -4 \\ -2 & 0 & 3 \\ 1 & 2 & -1 \end{bmatrix}](https://tex.z-dn.net/?f=%287%5C%2C%5Chat%5Cjmath%20-%204%5C%2C%5Chat%20k%29%20%5Ccdot%20%5Cbigg%28%28-2%5C%2C%5Chat%5Cimath%2B3%5C%2C%5Chat%20k%29%20%5Ctimes%20%28%5Chat%5Cimath%20%2B%202%5C%2C%5Chat%5Cjmath-%5Chat%20k%29%5Cbigg%29%20%3D%20%5Cdet%20%5Cbegin%7Bbmatrix%7D%200%20%26%207%20%26%20-4%20%5C%5C%20-2%20%26%200%20%26%203%20%5C%5C%201%20%26%202%20%26%20-1%20%5Cend%7Bbmatrix%7D)
Computing the determinant is easy with a cofactor expansion along the first column:
![\det \begin{bmatrix} 0 & 7 & -4 \\ -2 & 0 & 3 \\ 1 & 2 & -1 \end{bmatrix} = 2 \det \begin{bmatrix} 7 & -4 \\ 2 & -1 \end{bmatrix} + \det \begin{bmatrix} 7 & -4 \\ 0 & 3 \end{bmatrix} \\\\ = 2 + 21 = \boxed{23}](https://tex.z-dn.net/?f=%5Cdet%20%5Cbegin%7Bbmatrix%7D%200%20%26%207%20%26%20-4%20%5C%5C%20-2%20%26%200%20%26%203%20%5C%5C%201%20%26%202%20%26%20-1%20%5Cend%7Bbmatrix%7D%20%3D%202%20%5Cdet%20%5Cbegin%7Bbmatrix%7D%207%20%26%20-4%20%5C%5C%202%20%26%20-1%20%5Cend%7Bbmatrix%7D%20%2B%20%5Cdet%20%5Cbegin%7Bbmatrix%7D%207%20%26%20-4%20%5C%5C%200%20%26%203%20%5Cend%7Bbmatrix%7D%20%5C%5C%5C%5C%20%3D%202%20%2B%2021%20%3D%20%5Cboxed%7B23%7D)
c) Let
![z = f(x, y) = \dfrac{2x^2 + 2xy - 1}3](https://tex.z-dn.net/?f=z%20%3D%20f%28x%2C%20y%29%20%3D%20%5Cdfrac%7B2x%5E2%20%2B%202xy%20-%201%7D3)
Compute the partial derivatives and evaluate them at
:
![\dfrac{\partial f}{\partial x} = \dfrac{4x + 2y}3 \implies f_x(1,1) = 2](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cpartial%20f%7D%7B%5Cpartial%20x%7D%20%3D%20%5Cdfrac%7B4x%20%2B%202y%7D3%20%5Cimplies%20f_x%281%2C1%29%20%3D%202)
![\dfrac{\partial f}{\partial y} = \dfrac{2x}3 \implies f_y(1,1) = \dfrac23](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cpartial%20f%7D%7B%5Cpartial%20y%7D%20%3D%20%5Cdfrac%7B2x%7D3%20%5Cimplies%20f_y%281%2C1%29%20%3D%20%5Cdfrac23)
Then the tangent plane to
at (1, 1, 1) has equation
![z - 1 = 2 (x - 1) + \dfrac23 (y - 1) \implies \boxed{6x + 2y - 3z = 5}](https://tex.z-dn.net/?f=z%20-%201%20%3D%202%20%28x%20-%201%29%20%2B%20%5Cdfrac23%20%28y%20-%201%29%20%5Cimplies%20%5Cboxed%7B6x%20%2B%202y%20-%203z%20%3D%205%7D)
d) In polar coordinates,
is the set
![R = \left\{ (r, \theta) ~:~ 0 \le r \le 3 \text{ and } 0 \le \theta \le 2\pi \right\}](https://tex.z-dn.net/?f=R%20%3D%20%5Cleft%5C%7B%20%28r%2C%20%5Ctheta%29%20~%3A~%200%20%5Cle%20r%20%5Cle%203%20%5Ctext%7B%20and%20%7D%200%20%5Cle%20%5Ctheta%20%5Cle%202%5Cpi%20%5Cright%5C%7D)
Then the integral evaluates to
![\displaystyle \iint_R \frac{dA}{\pi\sqrt{x^2+y^2}} = \frac1\pi \int_0^{2\pi} \int_0^3 \frac{r\,dr\,d\theta}{\sqrt{r^2}} \\\\ = \frac1\pi \left(\int_0^{2\pi}d\theta\right) \left(\int_0^3dr\right) = 2\times3 = \boxed{6}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Ciint_R%20%5Cfrac%7BdA%7D%7B%5Cpi%5Csqrt%7Bx%5E2%2By%5E2%7D%7D%20%3D%20%5Cfrac1%5Cpi%20%5Cint_0%5E%7B2%5Cpi%7D%20%5Cint_0%5E3%20%5Cfrac%7Br%5C%2Cdr%5C%2Cd%5Ctheta%7D%7B%5Csqrt%7Br%5E2%7D%7D%20%5C%5C%5C%5C%20%3D%20%5Cfrac1%5Cpi%20%5Cleft%28%5Cint_0%5E%7B2%5Cpi%7Dd%5Ctheta%5Cright%29%20%5Cleft%28%5Cint_0%5E3dr%5Cright%29%20%3D%202%5Ctimes3%20%3D%20%5Cboxed%7B6%7D)
e) By the chain rule,
![\dfrac{\partial w}{\partial t} = \dfrac{\partial w}{\partial x} \dfrac{\partial x}{\partial t} + \dfrac{\partial w}{\partial y} \dfrac{\partial y}{\partial t}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cpartial%20w%7D%7B%5Cpartial%20t%7D%20%3D%20%5Cdfrac%7B%5Cpartial%20w%7D%7B%5Cpartial%20x%7D%20%5Cdfrac%7B%5Cpartial%20x%7D%7B%5Cpartial%20t%7D%20%2B%20%5Cdfrac%7B%5Cpartial%20w%7D%7B%5Cpartial%20y%7D%20%5Cdfrac%7B%5Cpartial%20y%7D%7B%5Cpartial%20t%7D)
Eliminating the parameter, we find
![(x + y^2) - (3x + y) = t - t \implies x = \dfrac{y^2 - y}2](https://tex.z-dn.net/?f=%28x%20%2B%20y%5E2%29%20-%20%283x%20%2B%20y%29%20%3D%20t%20-%20t%20%5Cimplies%20x%20%3D%20%5Cdfrac%7By%5E2%20-%20y%7D2)
so that
when
.
Compute derivatives:
![\dfrac{\partial w}{\partial x} = 14x^{13}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cpartial%20w%7D%7B%5Cpartial%20x%7D%20%3D%2014x%5E%7B13%7D)
![\dfrac{\partial w}{\partial y} = 1](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cpartial%20w%7D%7B%5Cpartial%20y%7D%20%3D%201)
![\begin{cases} x + y^2 = t \\ 3x + y = t \end{cases} \implies \begin{cases}\dfrac{\partial x}{\partial t} + 2y \dfrac{\partial y}{\partial t} = 1 \\\\ 3 \dfrac{\partial x}{\partial t} + \dfrac{\partial y}{\partial t} = 1 \end{cases}](https://tex.z-dn.net/?f=%5Cbegin%7Bcases%7D%20x%20%2B%20y%5E2%20%3D%20t%20%5C%5C%203x%20%2B%20y%20%3D%20t%20%5Cend%7Bcases%7D%20%5Cimplies%20%5Cbegin%7Bcases%7D%5Cdfrac%7B%5Cpartial%20x%7D%7B%5Cpartial%20t%7D%20%2B%202y%20%5Cdfrac%7B%5Cpartial%20y%7D%7B%5Cpartial%20t%7D%20%3D%201%20%5C%5C%5C%5C%203%20%5Cdfrac%7B%5Cpartial%20x%7D%7B%5Cpartial%20t%7D%20%2B%20%5Cdfrac%7B%5Cpartial%20y%7D%7B%5Cpartial%20t%7D%20%3D%201%20%5Cend%7Bcases%7D)
![\left(\dfrac{\partial x}{\partial t} + 2y\dfrac{\partial y}{\partial t}\right) - 2y \left(3\dfrac{\partial x}{\partial t} + \dfrac{\partial y}{\partial t}\right) = 1 - 2y \implies \dfrac{\partial x}{\partial t} = \dfrac{2y-1}{6y-1}](https://tex.z-dn.net/?f=%5Cleft%28%5Cdfrac%7B%5Cpartial%20x%7D%7B%5Cpartial%20t%7D%20%2B%202y%5Cdfrac%7B%5Cpartial%20y%7D%7B%5Cpartial%20t%7D%5Cright%29%20-%202y%20%5Cleft%283%5Cdfrac%7B%5Cpartial%20x%7D%7B%5Cpartial%20t%7D%20%2B%20%5Cdfrac%7B%5Cpartial%20y%7D%7B%5Cpartial%20t%7D%5Cright%29%20%3D%201%20-%202y%20%5Cimplies%20%5Cdfrac%7B%5Cpartial%20x%7D%7B%5Cpartial%20t%7D%20%3D%20%5Cdfrac%7B2y-1%7D%7B6y-1%7D)
![3\left(\dfrac{\partial x}{\partial t} + 2y \dfrac{\partial y}{\partial t}\right) - \left(3\dfrac{\partial x}{\partial t} + \dfrac{\partial y}{\partial t}\right) = 3 - 1 \implies \dfrac{\partial y}{\partial t} = \dfrac2{6y-1}](https://tex.z-dn.net/?f=3%5Cleft%28%5Cdfrac%7B%5Cpartial%20x%7D%7B%5Cpartial%20t%7D%20%2B%202y%20%5Cdfrac%7B%5Cpartial%20y%7D%7B%5Cpartial%20t%7D%5Cright%29%20-%20%5Cleft%283%5Cdfrac%7B%5Cpartial%20x%7D%7B%5Cpartial%20t%7D%20%2B%20%5Cdfrac%7B%5Cpartial%20y%7D%7B%5Cpartial%20t%7D%5Cright%29%20%3D%203%20-%201%20%5Cimplies%20%5Cdfrac%7B%5Cpartial%20y%7D%7B%5Cpartial%20t%7D%20%3D%20%5Cdfrac2%7B6y-1%7D)
Then at the point (1, 1), the derivative we want is
![\dfrac{\partial w}{\partial t} = 14 \times\dfrac3{11} + \dfrac2{11} = \dfrac{44}{11} = \boxed{4}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cpartial%20w%7D%7B%5Cpartial%20t%7D%20%3D%2014%20%5Ctimes%5Cdfrac3%7B11%7D%20%2B%20%5Cdfrac2%7B11%7D%20%3D%20%5Cdfrac%7B44%7D%7B11%7D%20%3D%20%5Cboxed%7B4%7D)